Knowledge of Signs and Symptoms of Heart Attack and Stroke among Singapore Residents. (10th April 2014) - Quah, Joy Li Juan; Yap, Susan; Cheah, Si Oon; Ng, Yih Yng; Goh, E. Shaun; Doctor, Nausheen; Leong, Benjamin Sieu-Hon; Tiah, Ling; Chia, Michael Yih Chong; Ong, Marcus Eng Hock
Abstract : Aim . To determine the level of knowledge of signs and symptoms of heart attack and stroke in Singapore resident population, in comparison to the global community. Methods . A population based, random sample of 7, 840 household addresses was selected from a validated national sampling frame. Each participant was asked eight questions on signs and symptoms of heart attack and 10 questions on stroke. Results. The response rate was 65.2% with 4, 192 respondents. The level of knowledge for preselected, common signs and symptoms of heart attack and stroke was 57.8% and 57.1%, respectively. The respondents scored a mean of 5.0 (SD 2.4) out of 8 for heart attack, while they scored a mean of 6.8 (SD 2.9) out of 10 for stroke. Respondents who were ≥50 years, with lower educational level, and unemployed/retired had the least knowledge about both conditions. The level of knowledge of signs and symptoms of heart attack and stroke in Singapore is comparable to USA and Canada. Conclusion . We found a comparable knowledge of stroke and heart attack signs and symptoms in the community to countries within the same economic, educational, and healthcare strata. However older persons, those with lower educational level and those who are unemployed/retired, require more public health education efforts.